2021
DOI: 10.3389/fimmu.2021.707463
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, Safety and Tolerability of a New 10% Intravenous Immunoglobulin for the Treatment of Primary Immunodeficiencies

Abstract: We report here the results of a phase 3 study to assess the efficacy, safety, and tolerability of GC5107, a new 10% liquid intravenous immunoglobulin (IVIG) in preventing serious bacterial infections in patients with primary immunodeficiency (ClinicalTrials.gov: NCT02783482). Over a 12-month study period, 49 patients aged 3 to 70 years with a confirmed diagnosis of primary immunodeficiency received GC5107 at doses ranging from 319 to 881 mg/kg body weight every 21 or 28 days, according to their previous IVIG m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Almost all patients achieved the maximum infusion rate specified in the product labeling, utilizing an infusion protocol with 15-minute rate escalation increments. Recent trials of other IVIG products have reported achieving per-protocol infusion rates in >90% of infusions, but with longer rate escalation increments (30 minutes vs 15 minutes for the IVIG formulations used in this analysis) ( 22 , 24 ). In our study, subgroup analyses demonstrated differences in achievement of the maximum infusion rate by groups, with higher probabilities of achieving the maximum rate for adults vs pediatric patients, males vs females, and infusions every 28 days vs every 21 days.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Almost all patients achieved the maximum infusion rate specified in the product labeling, utilizing an infusion protocol with 15-minute rate escalation increments. Recent trials of other IVIG products have reported achieving per-protocol infusion rates in >90% of infusions, but with longer rate escalation increments (30 minutes vs 15 minutes for the IVIG formulations used in this analysis) ( 22 , 24 ). In our study, subgroup analyses demonstrated differences in achievement of the maximum infusion rate by groups, with higher probabilities of achieving the maximum rate for adults vs pediatric patients, males vs females, and infusions every 28 days vs every 21 days.…”
Section: Discussionmentioning
confidence: 87%
“…The observed rates of product-related headache (6.1% of infusions, 28.5% of patients) and migraine (0.5% of infusions, 4.1% of patients) occurred with 94.6% of patients achieving the maximum infusion rate, and use of a 15-minute rate escalation protocol. To place these results in context, headache rates reported in recent studies of IVIG in PI range from 2% to 22% on a per-infusion basis, and from 8% to 50.8% on a per-patient basis ( 13 , 22 , 24 26 , 32 , 38 ). Our results cannot be compared directly with these trials due to differences in trial design, patient population, and other factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GC5107 is a 10% glycine-stabilized IVIG produced by GC Biopharma. Results of the phase 3 clinical trial in patients with primary immunodeficiency have been published previously (19). Here, we describe in detail the manufacturing process for GC5107 and demonstrate that cation exchange (CEX) chromatography is a robust means of removing FXIa from the final preparation, even in starting material spiked with high levels of FXIa.…”
Section: Introductionmentioning
confidence: 84%